Assessing the Benefits and Costs of Social Forestry Projects - Romm, Jeff (Indian Forester, 1980)
The purpose and effects of a social forestry project extend beyond the bounds of its plantation. As predictions performance, project analyses must incorporate them as well as plantations direct costs and returns. The critical features of project performance have drawn considerable attention in recent year. This paper is an attempt to translate them into a framework that can be used in project analysis. It proposes that a social forestry project be defines to include the area and population within which a plantation causes changes in the employment of land and labour, thus in the level and distribution of income. It also proposes a three-tiered mode of analysis to account for the distributive requirements of project viability: benefit-cost estimation for the project as a whole for the project as perceived separately by participating villages and departments, and for the project as perceived separately by groups of villagers for which its outcome are significant.